2021
DOI: 10.1080/17482631.2021.1961572
|View full text |Cite
|
Sign up to set email alerts
|

Towards an integrative self: a digital photo elicitation study of resilience among key marginalized populations of sexual and gender minority youth

Abstract: Purpose: Sexual and gender minority youth (SGMY) experience unique challenges related to identity and disclosure, and cope in vibrant ways. Qualitative research has not yet fulsomely explored the risk, resilience, and identity intersections that impact vulnerable SGMY wellbeing. Methods: This digital photo-elicitation study (QueerView) recruited thirty SGMY (aged 14–29) from priority populations that had one or more of the following experiences:  trans and gender diverse, homelessness, child welfare, and immig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…The direct participation of key populations is crucial for creating a positive community image, fostering inclusivity, and contributing to better social change [ 69 ]. The use of education and advocacy activities to empower these individuals facilitates meaningful interaction with the community [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The direct participation of key populations is crucial for creating a positive community image, fostering inclusivity, and contributing to better social change [ 69 ]. The use of education and advocacy activities to empower these individuals facilitates meaningful interaction with the community [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its ability to engage and empower participants to critically reflect on and make sense of the self, photo-elicitation is increasingly used as an inclusive strategy in research on sensitive issues (Rose, 2016; Wagner, 2011) exploring sexuality (Craig et al, 2020; 2021; Joy & Numer, 2017; Nguyen et al, 2018), sex work (Smith, 2015) and youth identities in post-conflict areas (Leonard & McKnight, 2014). In Craig et al’s (2021) constructivist grounded approach to examining resilience among sexual and gender minority youth, photo-elicitation strengthened the voice of youths and increased accessibility to diverse participants. Joy and Numer (2017) integrated researcher generated photographs into focus group interviews to examine participation in queer student advocacy group and found that photo-elicitation facilitated self-reflection and in-depth exploration of topics which contributed to thematic development.…”
Section: Photo Elicitation As a Visual Methodsmentioning
confidence: 99%
“…Ultimately, leaving the home was described as an act of self-preservation by youth in this study, some of whom said that they would have killed themselves had they remained at home. Craig et al (2021) similarly found that connecting to trans community was a powerful, positive experience for trans young people navigating homelessness and was an important part of developing a self-concept that allowed for resilience, even in challenging circumstances.…”
mentioning
confidence: 91%